Empowering joint business groups in managing fishery overproduction - Sadat, Anwar; Nazar, Asrul; Basir, Muh. Askal; Melati, Mawar (Universitas Muhammadiyah Magelang, 2025)
Overfishing is a pressing issue in coastal communities, threatening marine ecosystems and livelihoods. This community service program aimed to enhance the capacity of Joint Business Groups (KUBE) in processing excess fish catches into value-added products like fish floss. The activities were implemented using extension and mentoring methods for the “Melai” Joint Business Group. The results indicate that KUBE members gained skills in managing and processing surplus fish catches. The excess fish was transformed into various products, such as salted fish, fish floss, or other ready-to-eat items. Furthermore, the KUBE's income also increased after the program, opening up opportunities for product and market diversification.